Tinjauan Persepsi Anak Terhadap Kekerasan - Beatriks Novianti Kiling-Bunga; Indra Yohanes Kiling (Universitas Nusa Cendana, 2019)
Children are a group of individuals belong in an age group that is vulnerable to various kind of negative behaviours. Neglection, abuse, and also violence are some of the negatives that often happens to children. Children’s perception of violence influences their reaction to violence itself. This paper discusses the concept of perception and also its concepts and then relate it in children’s context. Development aspects and a variety of violence were discussed in this paper. Concepts of perception were reviewed in detail by considering development tasks and also development aspects of children. Violence was looked from the global perspective by considering the type of violence that often happens to children. Factors that cause violence were carefully reviewed to help in forming an effective intervention. A good intervention should consider deeply the complexity of the violence phenomenon in children. Activists and academia who are working in this field could consider more of children’s perception to violence conceptsin doing related works.